PROFIL KONSEP DIRI MAHASISWA UNIVERSITAS PGRI ADI BUANA SURABAYA (UNIPA) - Hartanti, Jahju; Marfu’i, Lucky Nindi Riandika (Jurnal Bimbingan dan Konseling Terapan, 2019)
Self-concept is one component that describes itself due to the experience of interaction with the environment. The purpose of this study was to identify the level of self-concept of Universitas PGRI Adi Buana Surabaya students. In addition, this research is used as an empirical study in developing personal-social guidance programs for UNIPA students. This study uses a quantitative approach with survey methods. The results of this study illustrate that the level of self-concept of Universitas PGRI Adi Buana Surabaya students is in the positive category with a percentage of 93.18%. The data can be used as a reference in the development of curative social-personal guidance programs for students at the Universitas PGRI Adi Buana Surabaya (UNIPA). Based on the results of the research obtained, where the self-concept of students has a low category on personal self, physical self, moral ethical self, and self identity can be a reference for the preparation of hypothetical counseling and guidance service programs.